Synthesis and Characterization of Molecular Imprinting Polymer Microspheres of Piperine: Extraction of Piperine from Spiked Urine - Rachel Marcella Roland; Showkat Ahmad Bhawani (Journal of Analytical Methods in Chemistry)
Molecularly imprinted polymer (MIP) microspheres for Piperine were synthesized by precipitation polymerization with a noncovalent approach. In this research Piperine was used as a template, acrylic acid as a functional monomer, ethylene glycol dimethacrylate as a cross-linker, and 2,2′-azobisisobutyronitrile (AIBN) as an initiator and acetonitrile as a solvent. The imprinted and nonimprinted polymer particles were characterized by using Fourier transform infrared spectroscopy (FT-IR) and Scanning Electron Microscopy (SEM). The synthesized polymer particles were further evaluated for their rebinding efficiency by batch binding assay. The highly selected imprinted polymer for Piperine was MIP 3 with a composition (molar ratio) of 0.5 : 3 : 8, template : monomer : cross-linker, respectively. The MIP 3 exhibits highest binding capacity (84.94%) as compared to other imprinted and nonimprinted polymers. The extraction efficiency of highly selected imprinted polymer of Piperine from spiked urine was above 80%.